Prenatally Diagnosed Cardiac Tumors and Tuberous Sclerosis Complex: A Single-Center Experience - Matija Bakoš; Dora Jelinek; Ana Ćorić Ljoka; Nada Sindičić Dessardo; Dalibor Šarić; Ruža Grizelj (Children)
Background/Objectives: Cardiac rhabdomyoma (CR), the most frequently occurring fetal cardiac tumor, is often an early marker of tuberous sclerosis complex (TSC). This study evaluates outcomes of fetuses with prenatally diagnosed cardiac tumors managed at a single tertiary center. Methods: Medical records of fetuses diagnosed with cardiac tumors between 2009 and 2024 were retrospectively reviewed. Results: Sixteen cases were identified, with a median follow-up of 6.7 years. TSC was confirmed in 14 cases (88%). Multiple tumors were observed in 13 cases (81%), while 3 cases (19%) had solitary tumors. Both non-TSC cases involved solitary tumors. Cardiac complications (arrhythmias, conduction disorders, and hemodynamic abnormalities) occurred in 38% of cases prenatally and 69% postnatally, with larger tumor diameters significantly associated with complications (p = 0.02). No fetal hydrops or mortality occurred; however, one child died at age five due to a seizure. Postnatal tumor regression occurred in 56% of cases and complete regression in 38% by a median age of 2.3 years (range: 0.6–4.4). One tumor remained stable. Brain MRI revealed TSC-related changes in all TSC-affected patients except one, who had a developmental brain anomaly. Most TSC patients experienced epilepsy (71%) and developmental delays. Conclusion: While CRs are typically benign and regress spontaneously, their strong association with TSC highlights the importance of early diagnosis and family counseling. TSC-related epilepsy and psychomotor delays significantly impair the quality of life. Early mTOR inhibitor therapy offers promise in mitigating TSC-related complications and improving outcomes.